2020
DOI: 10.1111/nph.16495
|View full text |Cite
|
Sign up to set email alerts
|

Systemin‐mediated long‐distance systemic defense responses

Abstract: Systemin, a peptide plant hormone of 18 amino acids, coordinates local and systemic immune responses. The activation of the canonical systemin-mediated systemic signaling pathway involves systemin release from its precursor prosystemin, systemin binding to its membrane receptor SYSTEMIN RECEPTOR1 (SYR1), and the transport of long-distance signaling molecules, including jasmonic acid, the prosystemin mRNA, volatile organic compounds and possibly systemin itself. Here, we review emerging evidence that the disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 98 publications
(131 reference statements)
1
23
0
1
Order By: Relevance
“…Since cell-cell transportation of JA involves both influx and efflux across plasma membranes, it is likely that other JATs, such as the JA exporters AtJAT1 [47] and another potential JA exporter, AtJAT5 [48], are involved. These findings support the idea that JA may act as one component of the mobile molecular signatures in stress-or wound-induced systemic responses [53].…”
Section: Jasmonate Transporters (Jats)supporting
confidence: 86%
See 1 more Smart Citation
“…Since cell-cell transportation of JA involves both influx and efflux across plasma membranes, it is likely that other JATs, such as the JA exporters AtJAT1 [47] and another potential JA exporter, AtJAT5 [48], are involved. These findings support the idea that JA may act as one component of the mobile molecular signatures in stress-or wound-induced systemic responses [53].…”
Section: Jasmonate Transporters (Jats)supporting
confidence: 86%
“…JA has also been reported to be involved in a wide range of abiotic stress responses, including salt, drought, heavy metal, high and low temperature, light stress and ozone stress [23,127]. Furthermore, mounting evidence suggests that JA and its precursors, such as OPDA, participate in systemic signaling in plants, through which local stress can be perceived throughout the entire plant to induce systemic defense response or systemic acquired acclimation (SAA) [47,49,53,[170][171][172][173].…”
Section: Figurementioning
confidence: 99%
“…JAs-mediated growth-to-defense tradeoffs regulate plant defense against necrotrophic pathogens and insect herbivores [ 16 , 17 ]. In previous studies, many genes of the JA signaling pathway were identified as participants of plant defense [ 18 20 ]. By the crosstalk with other phytohormones, JAs take part in the defense against abiotic stresses and biotic stresses [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systemin was found in most species of the Solanaceae family (Ryan and Pearce 2003). Treatment of tomatoes with systemin triggers an array of resistance responses, including the production of proteinase inhibitors, the induction of extracellular alkalization and ethylene emission, and defense against insect herbivory (Zhang et al 2020a). PEP1, a 23-aa peptide, is the first phytocytokine identified in Arabidopsis.…”
Section: Classification Identification and Function Of Phytocytokinesmentioning
confidence: 99%